Comparing zirconia to anterior strip crowns in primary anterior teeth in children: a randomized clinical trial - Sumer M. Alaki (BMC Oral Health, 2020)
Abstract Background Providing restorations to anterior teeth in children is a challenging task due to the need for high esthetics, strength, and durability. This study was done to compare prefabricated primary zirconia with resin composite strip crowns on primary maxillary central and lateral incisors with regards to gingival health, plaque accumulation, recurrent caries, restoration failure, and opposing teeth wear over a period of 3, 6 and 12 months. Methods Children attending the King Abdulaziz University, Faculty of Dentistry (KAUFD) clinics who needed restorations were screened for inclusion criteria. A total of 120 teeth were treated; 60 with zirconia and 60 with strip crowns. Randomization was done by simple random allocation using SPSS software version 20.0 (Armonk, NY; IBM Corp.). A simple descriptive statistic was used for analysis by Wilcoxon Signed-Rank test and Chi-square test. Level of significance was set at (α = 0.05) and level of confidence at (95%). The presented research was registered retrospectively at ClinicalTrials.gov in 6th of August 2017, under registration number NCT03184012. Results Zirconia crowns showed significantly less gingival bleeding at the 3- and 6-months follow up periods (p < 0.006, p < 0.001; respectively), less plaque accumulation at all follow up visits (p < 0.001), no restoration failure (p < 0.001), but more wear to opposing teeth (p < 0.02). No significant difference was found between the two crowns with regards to recurrent caries (p < 0.135). Conclusion Based on our data we conclude that overtime teeth covered with zirconia crowns show better gingival health and less bleeding, plaque accumulation as well as less loss of material. On the other hand, zirconia can cause more loss of opposing tooth structure.